Study of 9mm Improvised Pistol Pattern & Gunshot Residue with respect to Different Range - Sahu, Karen Isha; Kennao, Puleno; Gupta, AK; Saran, Vaibhav; Waghmare, NP (International Journal of Computer Sciences and Engineering, 2025)
Armed violence is quite common in India and among the other top states; Delhi and its National capital region (NCR) play an imperative role when it comes to seizures of the country made firearms. Thus, Forensic firearm examination of gunshot residue (GSR) has become indispensable. This study presents the characteristics of the seized semiautomatic 9mm Improvised pistol and the gunshot pattern formed on the cloth target after firing in Forensic Science Laboratory, Delhi, India. This study also emphasizes the analysis of GSR particles deposited on the cotton cloth by Improvised Semiautomatic Pistol using standard ammunition at different shooting distance (5cm & 10cm). The collection and analytical method allowed elemental detection of Sb, Ba, Cu, Pb, and Ni on ppm level by Atomic Absorption Spectroscopy (AAS) analysis. In this study we observed that when the muzzle diameter and barrel length were constant, the gunshot pattern varied whereas for gunshot residue, out of all the five elements (Sb, Ba, Cu, Pb, and Ni), only the amount of Sb, Pb and Ni were seen to be increased with increased range from 5cm to 10cm.